Investigation into the molecular interaction between forkhead box P3 (FOXP3) and vitamin D receptor (VDR) - Hurwitz, Jessica Sarah (University of the Witwatersrand, Johannesburg, 2025)
Forkhead box P3 (FOXP3) is a transcription factor that is essential in the differentiation of T cells into regulatory T cells (Tregs), which play a critical role in regulating the adaptive immune system. FOXP3 expression is in turn regulated by the vitamin D receptor (VDR) and its ligand, 1,25-dihydroxyvitamin D3 (1,25(OH)D3). VDR is a transcription factor with a diverse range of functions, including immune regulation. However, whether these two proteins cooperatively regulate the immune system through direct interaction following FOXP3 expression is yet unknown. This study aimed to determine whether the VDR ligand binding domain (LBD) and the DNA-binding forkhead domain (FHD) of FOXP3 interact in the presence and absence of 1,25(OH)D3. Computational and experimental interaction studies were performed for cross-verification. An in silico study was done using LZerd and HDock to predict if the LBD of VDR interacted with the FHD of FOXP3 in the presence and absence of 1,25(OH)D3. For the experimental studies, these domains were thus overexpressed in E. coli cells, purified using immobilised metal affinity chromatography, and were then structurally and functionally characterised. After successful overexpression and purification, the interaction was further studied in vitro using fluorescence anisotropy. VDR LBD was found to interact at helix 3 (the DNA binding helix) of FOXP3 FHD in silico when both in the presence and absence of 1,25(OH)D3. Additionally, VDR LBD and FOXP3 FHD were found to interact in vitro only in the presence of 1,25(OH)D3 with a Kd of 0.2 μM. No interaction occurred in the absence of 1,25(OH)D3 in vitro. Thus, a medium affinity protein-protein interaction between the two immune regulatory proteins, VDR LBD and FOXP3 FHD, was discovered for the first time in this study, and 1,25(OH)D3 was identified as being a key player in this interaction, furthering our understanding of their important role in the coregulation of the immune system.
A dissertation submitted in fulfilment of the requirements for the degree Master of Science, to the Faculty of Science, School of in Molecular and Cell Biology, University of the Witwatersrand, Johannesburg, 2025
Keywords: Autoimmune disorders; Fox proteins; vitamin D receptor; Vitamin D; Protein interactions; UCTD; SDG-3: Good health and well-being; SDG-9: Industry, innovation and infrastructure